The complete mitochondrial genome of a bagrid catfish, Tachysurus nudiceps, and its phylogenetic implications for the classification of the bagrid genera - Syuri Hashimoto; Ryosuke Kakehashi; Tsuyoshi Mori; Chiaki Kambayashi; Shigefumi Kanao; Atsushi Kurabayashi (Mitochondrial DNA. Part B. Resources, 2022)
The complete sequence of the mitochondrial genome (mitogenome) of Tachysurus nudiceps (family Bagridae; order Siluriformes) was determined using next-generation sequencing. The composition of its mitogenome is the same as that observed in most other vertebrates and consists of 37 genes, an L-strand replication origin and a control region. As in previous studies, our phylogenetic analyses revealed that many of the bagrid genera are not monophyletic, emphasizing the necessity for reviewing and revising the taxonomy of this family at the genus level.